Psoriasis and Diabetes, a Dangerous Association: Evaluation of Insulin Resistance, Lipid Abnormalities, and Cardiovascular Risk Biomarkers - Brazzelli, Valeria; Maffioli, Pamela; Bolcato, Vittorio; Ciolfi, Christian; D'Angelo, Angela; Tinelli, Carmine; Derosa, Giuseppe (Frontiers in Medicine, 2021)
Aims: Psoriasis is an immune-mediated dermatosis with cardio-metabolic comorbidities. The aim of this study was to assess insulin-resistance, lipid abnormalities and cardiovascular risk biomarkers in psoriatic patients with or without type 2 diabetes mellitus (T2DM). Materials and methods: We enrolled 425 patients: 86 psoriatics, 69 psoriatic with T2DM, 120 T2DM patients and 150 healthy subjects. We measured Psoriasis Area and Severity Index (PASI), body mass index (BMI), insulin-resistance parameters [glycosylated hemoglobin (HbA1c), fasting plasma glucose (FPG), fasting plasma insulin (FPI), with homeostasis model assessment index (HOMA index)], lipidic panel, plasminogen activator inhibitor-1 (PAI-1), homocysteine, soluble adhesion molecules, matrix metalloproteinase, adipocytokines. Results: FPG, HbA1c and HOMA-IR were higher in diabetics with psoriasis (p<0.0001) than psoriatics. FPI levels were higher in diabetics with psoriasis than in diabetics and psoriatics (p<0.0001), and higher in psoriatic than controls (p<0.0001). Psoriatics and diabetics with psoriasis showed higher triglyceride and LDL-C levels (p<0.0001) than diabetics. Homocysteine was higher in psoriatics and diabetics with psoriasis (p<0.0001) than in diabetics. PAI-1 was higher in diabetics with psoriasis than diabetics (p<0.01). sICAM-1 and sVCAM-1 was higher in diabetics with psoriasis than diabetics (p<0.001 and p<0.01) and psoriatics (p<0.001 and p<0.0001). Visfatin and resistin were lower in psoriatics (p<0.0001) and in diabetics with psoriasis (p<0.001 and p<0.0001, respectively) than diabetics. Conclusions: A limitation of this study is that there is a significant difference in mean age between controls and other study groups: the lack of matching between case and control groups may interfere with the external validity of the study findings. Considering this, the study highlights pathogenetic link between psoriasis, considered a pre-diabetic condition, and diabetes. Insulin-resistance seems to be the keystone of psoriasis’ comorbidities. Psoriasis reinforces diabetes, causing a greater cardiometabolic risk.